Association Between Low Bone Mineral Density Risk Factors and Estrogen Receptor ? Gene Polymorphisms in Japanese Female Athletes - Tetsuro Kobayashi; Inkwan Hwang (Mary Ann Liebert, 2021)
Background: The relationship between bone metabolism-related gene polymorphisms and low bone mineral density (BMD) risk factors in female athletes is unclear. This study aimed at investigating whether the sensitivity of low BMD risk factors to BMD depends on estrogen receptor ? (ER?) gene polymorphisms in Japanese female athletes. Materials and Methods: This study included 280 collegiate female athletes from 12 competitive sports (age, 19.2???1.3 years). Data on sports participation, age at menarche, menstrual cycles, prior stress fractures, and prior eating disorders were obtained through a questionnaire-type survey. Sports types were classified into endurance, esthetic, aquatic, ball, and high load in consideration of exercise load characteristics. ER? gene PvuII (rs2234693) and XbaI (rs9340799) polymorphisms were analyzed by TaqMan? assay. The total body BMD was measured by dual-energy X-ray absorptiometry. Results: On multiple regression analysis, sports types, body mass index (BMI), menarche, and XbaI polymorphism remained robust independent predictors of BMD. However, prior stress fractures and menstrual cycles were excluded. In athletes carrying the XX+Xx genotype of XbaI polymorphism, sports types and BMI were associated with BMD. However, in athletes carrying the xx genotype of XbaI polymorphism, sports types, BMI, and menarche were associated with BMD. These results indicated that athletes carrying the xx genotype with delayed menarche had low BMD. Conclusions: In collegiate female athletes, participation in endurance, esthetic, and aquatic sports types and a low BMI are associated with low BMD. In addition, delayed menarche may negatively affect BMD in athletes carrying the xx type of ER? gene XbaI polymorphism.